When do children begin to care for others? The ontogenetic growth of empathic concern across the first two years of life - Paulus, Markus; Becher, Tamara; Christner, Natalie; Kammermeier, Marina; Gniewosz, Burkhard; Pletti, Carolina (Cognitive development, 2024)
Empathic concern for others plays a central role for human cooperation and is proposed to be key in moral development. Developmental theories disagree on the age of emergence of empathic concern in human ontogeny and the factors supporting its early development. To assess different theoretical views, the current study longitudinally assessed infants’ (N = 127) reactions towards an experimenter and their mothers simulating pain at 6, 10, 14, and 18 months. As an emotional control condition, infants’ reactions towards a laughing experimenter were assessed. Maternal sensitivity, children’s temperamental emotionality, and self-recognition were included as predictors. True intraindividual change models were applied to capture the growth of empathic concern in early development. Overall, there were minor and inconsistent differences in children’s responses to laughing and crying others in the first year of life, whereas clear differences emerged in the second year. At 6 months, scale values of empathic concern were significantly related to measures of infant distress suggesting that infants experience emotional contagion and not veridical empathic concern. At 18 months, children’s concern towards the experimenter was related to their concern towards their mother. Maternal sensitivity, negative emotionality and self-recognition were related to children’s empathic concern within the second year. These findings suggest that empathic concern emerges in the second year and point to a gradual emergence of concern for others in human ontogeny. •We explored the ontogeny of concern for others in early childhood.•Infants do not show concern for others that is specific to others’ suffering.•Concern for others emerges in the second year.•Self-other-understanding and maternal sensitivity related to other-oriented concerns in toddlerhood.